Anesthesic treatment for an urgent cesarean in a pregnant patient suffering from morbid obesity. A case report. - Bárbara Cabezas Poblet; Rolando Espin González; Práxedes Rojas Santana (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Morbid obesity is not a condition frequently found in patients under surgical treatment. However, its prevalence in the last decades tends to rise which may have a profound impact in the anesthetic morbid-mortality. These risks are increased in the case of pregnant patients. For these reasons a case of a pregnant woman is presented. She is suffering from morbid obesity when was announced to be surgically treated in emergency due to a cesarean at the University Hospital Dr. Gustavo Aldereguía Lima in Cienfuegos.